Dynamique forestière post-conflits armés de la Forêt classée du Haut-Sassandra (Côte d’Ivoire) - Charles Yao Sangne; Yao Sadaiou Sabas Barima; Issouf Bamba; Claude-Thierry Aké N’Doumé (VertigO)
The classified forest of Haut-Sassandra which is considered as the best protected classified forest of Côte d’Ivoire, knows several intrusions in its conventional limits supported by the military political crisis in the country, and which lasted from 2002 till 2011. Several pioneers fronts were opened and entailed the clearing of several thousand hectares of natural forests followed by installation of cash crop in particular the cocoa. In this context, the present work tries to estimate the remaining forest surfaces of this protected area mainly in the North, previously controlled by armed groups rebel to Governement authority. On the one hand, this work aims to map the land use of the North of the classified forest of Haut-Sassandra and its periphery in 2001 and 2013 ; and on the other hand to follow the dynamics of the forest cover and these land use types from 2001 till 2013. To achieve these objectives, two Spot images from Spot 4 of 14/12/2001 (scene 190.53) and Spot 5 of 28/12/2013 (scene 192.53) were acquired and treated. This study revealed that the surfaces of the natural rain forests strongly declined and passed from 37749.06 hectares in 2001 to 7 844.62 hectares in 2013 (that is 79.22 %). On the contrary, the surfaces of mosaics fallows-cultures strongly increased and passed from 9 909.74 hectares to more than 36 374 hectares. Of the forest massif of the North of the classified forest of Haut-Sassandra, it remains only scraps of generally degraded forests today.